2020
DOI: 10.18388/abp.2020_2848
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptor activity landscape in rat and human glioma cell lines

Abstract: P2X7 is a commonly expressed purinergic receptor, which functions as a cation-permeable channel in the plasma membrane. In certain circumstances, the receptor may also form a large transmembrane pore what results in cell death. P2X7 receptors control numerous physiological and pathological cellular processes and their overexpression is often associated with cancer progression. As nucleotides are important signaling molecules in the central nervous system, P2X7 plays also an important but ambiguous role in glio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
3
7
0
1
Order By: Relevance
“…The antibodies used have been validated previously in multiple studies 24,44,45 . These findings are consistent with previous published data that have demonstrated that P2X7R is present in other glioblastoma cell lines, human glioma samples and orthotopic glioma animal models 16,27,29,46 . The GM-CSF receptor consists of both an α and a β subunit which are necessary for receptor function and signaling 33 .…”
Section: Discussionsupporting
confidence: 93%
“…The antibodies used have been validated previously in multiple studies 24,44,45 . These findings are consistent with previous published data that have demonstrated that P2X7R is present in other glioblastoma cell lines, human glioma samples and orthotopic glioma animal models 16,27,29,46 . The GM-CSF receptor consists of both an α and a β subunit which are necessary for receptor function and signaling 33 .…”
Section: Discussionsupporting
confidence: 93%
“…Human glioma cell lines U-251 and U-138 are characterized by a low P2X7 expression when compared to rat glioma C6 cells, as was described previously [43]. Nevertheless, we observed an increase of p38 MAPK phosphorylation and increase of HSPA1 and CD133 protein level in U-138 glioma cells stimulated with 100 μM of BzATP for 24 h (Fig.…”
Section: Activity Of P2x7 Receptor In Human Gliomassupporting
confidence: 85%
“…In our previous study, we did not observe P2X7 stimulant effect on human U-251 and U-138 glioma cell proliferation. Moreover, P2X7 receptor seemed to be inactive in U-138 glioma cells [43]. In the present study, we showed the stimulant effect of P2X7 on p38 MAPK phosphorylation and CD133 and HSPA1 expression in U-138 cells.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In response to inflammation[ 14 , 128 ], trauma or injury[ 91 , 141 ], the elevation of ATP causes a prolonged stimulus that induces the transition of the ion channel to a nonselective membrane pore[ 101 , 142 , 143 ], making the cell permeable to molecules up to 900 daltons[ 94 , 101 , 142 , 143 ]. In association, massive calcium influx[ 144 ] can contribute to cell death[ 85 , 137 , 145 ], with subsequent release of greater amounts of ATP[ 146 - 148 ].…”
Section: The Purinergic Receptorsmentioning
confidence: 99%